2011
DOI: 10.1590/s0006-87052011000100029
|View full text |Cite
|
Sign up to set email alerts
|

O tratamento pré-colheita com aminoetoxivinilglicina ou ácido giberélico preserva a qualidade pós-colheita de ameixas 'Laetitia'

Abstract: O objetivo deste trabalho foi avaliar os efeitos do tratamento pré-colheita com aminoetoxivinilglicina (AVG; 0, 90, 120 mg L-1) e ácido giberélico (GA3; 0 e 100 mg L-1) sobre a qualidade de ameixas 'Laetitia' após o armazenamento refrigerado. A aplicação do AVG e do GA3 foi realizada, respectivamente, a sete e 28 dias antes do início da colheita comercial dos frutos. Os frutos foram armazenados em câmara frigorífica comercial durante 22 dias a 0,5 ºC e 92% de umidade relativa (UR), mais cinco dias de exposição… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This indicates both an increase in the crop productivity (overall yield) and a hastening of fruit ripening (higher yields in the first and second harvest, and reduction in the third). These results confirm the ethephon property of inducing an earlier color change in fruit peel, as reported by Powers and coauthors [19], Carvalho and coauthors [20], Delú Filho and coauthors [21], and Steffens and coauthors [22]. Moreover, the harvest of a higher fruit proportion in the Brazilian Archives of Biology and Technology.…”
supporting
confidence: 89%
“…This indicates both an increase in the crop productivity (overall yield) and a hastening of fruit ripening (higher yields in the first and second harvest, and reduction in the third). These results confirm the ethephon property of inducing an earlier color change in fruit peel, as reported by Powers and coauthors [19], Carvalho and coauthors [20], Delú Filho and coauthors [21], and Steffens and coauthors [22]. Moreover, the harvest of a higher fruit proportion in the Brazilian Archives of Biology and Technology.…”
supporting
confidence: 89%
“…In the 2015/16 harvest, the SS content was higher in control treatment fruits and in fruits that received mixed AVG application combined with ethephon (Table 3). According to Steffens et al (2011), high SS values may be related to high content of soluble pectins, since these fruits had the lowest pulp firmness values and lower pulp penetration and skin rupture strength (Table 4), demonstrating faster ripening of control treatment fruits. On the other hand, after the cold storage period, TA and SS/TA ratio were not influenced by treatments in both harvests (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…also found higher pulp firmness in apples treated with AVG. According to Steffens et al (2011), fruit texture response to AVG treatments is directly related to its effect on reducing ethylene production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fruit growing, biostimulants that inhibit the synthesis or action of ethylene have been used to retard ripening and preserve fruit quality during storage. In plums, Steffens et al (2011) found that the preharvest application of aminoethoxyvinylglycine (AVG) and gibberellic acid (GA 3 ) influenced fruit quality after refrigerated storage when applied alone. Luo, Chen and Xie (2011) verified the effect of salicylic acid on plums; the treated fruits presented a delay in the climacteric peak and the inhibition of respiration and ethylene production due to delayed polyphenoloxidase (PPO) and peroxidase (POD) activity and lower polyamine (PA) levels.…”
Section: Introductionmentioning
confidence: 99%